Аналіз фінансової стійкості підприємств - Пушкар, Олександр Іванович; Передерій, Ганна Дмитрівна (НТУ "ХПІ", 2017)
У статті розглянуто поняття фінансова стійкість підприємства, об'єктивна оцінка фінансової стійкості підприємства як основа його життєздатності є важливим інформаційним джерелом для обґрунтування і прийняття оптимального управлінського рішення, щодо суб'єкта господарювання. Розкрито сутність фінансової стійкості як економічної категорії. Висвітлено основні підходи до оцінки фінансової стійкості підприємств. Виділено основні показники фінансової стійкості сільськогосподарських підприємств.

The article considers the concept of financial sustainability of an enterprise, an objective assessment of the financial sustainability of the enterprise as the basis of its viability is an important source of information for subst antiating and adopting an optimal management decision regarding the subject of management. The essence of financial stability as an economic category is revealed. The main approaches to assessing financial stability of enterprises are highlighted. The basic indicators of financial stability of agricultural enterprises are allocated.
Analysis of financial sustainability of enterprises
Keywords: фінансовий стан; фінансова рівновага; фінансова нестійкість; оцінка; financial stability; financial condition; financial position; financial equilibrium; financial instability; analysis; evaluation